1980
DOI: 10.1007/bf00389727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with mueller total hip endoprostheses of different design and material

Abstract: Patients of the Orthopaedic University Hospital in Frankfurt operated between 1970 and 1977 were examined to control the success of implantations of total hip endoprostheses. Ninety-three percent of totally 1497 implanted hip prostheses are Müller standard type, additionally there have been implanted 44 Weber-Huggler prostheses and 54 special long stem prostheses. During the follow-up period of 10 years 7.4% of the primarily implanted prostheses had to be revised. The reasons for revision were loosening of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…In fact, the Christiansen prostheses with a long neck had a greater tendency toward medial migration than the heads with medium or short necks in our series. Similar observations have been made by Willert et al ( 1980) concerning different designs of Miiller total hip prostheses. When calculating a total offset as a sum of the structural offset of the Christiansen prosthesis and the offset resulting from the position of the stem, we could substantiate this theory further, demonstrating increased frequency of cement fractures and medial migration with increased total offqet due to long neck and varus position.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In fact, the Christiansen prostheses with a long neck had a greater tendency toward medial migration than the heads with medium or short necks in our series. Similar observations have been made by Willert et al ( 1980) concerning different designs of Miiller total hip prostheses. When calculating a total offset as a sum of the structural offset of the Christiansen prosthesis and the offset resulting from the position of the stem, we could substantiate this theory further, demonstrating increased frequency of cement fractures and medial migration with increased total offqet due to long neck and varus position.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, insertion of the stem in a varus position was more common in the Christiansen than in the Charnley group. Varus position has previously been found to predispose to loosening (Beckenbaugh & Ilstrup 1978, Willert et al 1980 Willert et al 1980). We observed that, to give maximal protection against loosening, the cement mantle has not only to cover the total length of the prosthetic stem but also to extend from cortical wall to cortical wall of the medullary canal.…”
Section: Discussionmentioning
confidence: 61%
“…Apart from one report of 11% stem fractures with the Muller prosthesis of the earlier design (Martens et al 1974), less than 5% of stem fractures have been reported with other prostheses (Chamley 1975, Carlsson et al 1977, Willert et al 1980, Chao and Coventry 1981, Wroblewski 1982, Ritter and Campbell 1986, Amstutz et al 1990. Munuera and GarciaCimbrelo 1990.…”
Section: Discussionmentioning
confidence: 97%
“…Unpredictable adverse reactions to some commonly used traditional implants have been reported by a number of research groups. [3][4][5][6][7] Key factors in device failure are believed to be the generation of wear particles and the biological response to them in periprosthetic tissues [2,4] as well as the degradation products of biodegradable materials, both resulting in osteolytic reactions. [5,6,8] The presence of activated macrophages [9][10][11][12][13] or foreignbody giant cells, [9,11,13] and the formation of a fibrous capsule [14,15] are tissue-specific responses that have been the focus of investigation in the evaluation of biomedical implants.…”
Section: Introductionmentioning
confidence: 99%